2007
DOI: 10.1055/s-0031-1278263
|View full text |Cite
|
Sign up to set email alerts
|

Delayed pseudoaneurysm repair: A case report

Abstract: Iatrogenic pseudoaneurysms are a complication of arterial catheterization performed for both diagnosis and intervention. Their incidence is approximately 1% following diagnostic catheterizations and 3.2% after interventional procedures. The symptoms of iatrogenic pseudoaneurysm are pain and swelling. The preferred method of treatment consists of thrombin injection under ultrasound guidance, although compression can be used. Most published research describes pseudoaneurysms that occurred close to the time of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Their incidence is 1% following diagnostic catheterizations and 3.2 to 7.7% after interventional procedures. 1 Diagnosis of iatrogenic pseudoaneurysms relies on a high index of suspicion by the clinician. They are diagnosed clinically with real-time duplex ultrasonography.…”
mentioning
confidence: 99%
“…Their incidence is 1% following diagnostic catheterizations and 3.2 to 7.7% after interventional procedures. 1 Diagnosis of iatrogenic pseudoaneurysms relies on a high index of suspicion by the clinician. They are diagnosed clinically with real-time duplex ultrasonography.…”
mentioning
confidence: 99%
“…3 This modality has the advantage of being efficacious in both acute and chronic pseudoaneurysms as it can be used in pseudoaneurysms up to 2 years old. 14 UGTI is also not impacted by anticoagulation. Schneider et al demonstrated in their series of UGTI an overall 97% efficacy of thrombin injection in all of their patients, and their anticoagulation status (19% of the patients) had no impact on the efficacy of pseudoaneurysm thrombosis.…”
Section: Ultrasound-guided Thrombin Injectionmentioning
confidence: 86%
“…The success rate using ultrasound-guided compression therapy is only 60 to 93%. [14][15][16] The disadvantages of the procedure include increased time for the ultrasonographer, pain for the patient, prolonged hospital stay due to the need for multiple attempts, and postprocedure surveillance, and increased failure rates with anticoagulation. 14 Ultrasound-guided compression therapy has the advantage of a lower chance of occlusion of the native vessel due to thrombus propagation with thrombin administration and no risk of the side effects associated with the systemic injection of thrombin.…”
Section: Compression Therapymentioning
confidence: 99%
See 2 more Smart Citations